(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mardiastuti A, Masy’ud B, Ginoga LN, Sastranegara H, Sutopo. 2021. Short Communication: Wildlife species used as traditional medicine by local people in Indonesia. Biodiversitas 22: 329-337. Since a long time ago, wild animals (wildlife species) have been used by the local people as traditional medicine. Research has been conducted in some areas, but there was no study that incorporates all data. The objective of this research was to collect nation-wide information on the wildlife species (mammals, birds, reptiles, amphibians) used as traditional medicine, identify the species used the most, and collect information on the diseases that were believed can be cured by the wildlife species. Papers and reports from previous studies were collected and analyzed. Based on 55 published scientific papers, 114 wildlife species were known to be used by the local people as traditional medicine (59 species of mammals, 12 birds, 37 reptiles, 6 amphibians). Reptiles were used more intensively and believed may cure many diseases, mainly respiratory, digestive, skin, and musculoskeletal diseases. Among all species, Reticulated Python (Malayopython reticulatus), Common Water Monitor (Varanus salvator), Tokay Gecko (Gekko gecko), Common Sun Skink (Eutropis multifasciata), and Malayan Porcupine (Hystrix brachyura) were listed as the most popular species for traditional medicine. As some species have already listed as protected and endangered, a necessary precautionary program is needed to ensure the harvest sustainability and survival of the endangered species.